The three sisters : acid gas injection, carbon capture and sequestration, and enhanced oil recovery /: acid gas injection, carbon capture and sequestration, and enhanced oil recovery. (2019) - (Petroleum engineer), Wu, Ying; Carroll, John J, 1958-; Hu, Yongle
No abstract available